JNK1 controls dendritic field size in L2/3 and L5 of the motor cortex, constrains soma size, and influences fine motor coordination - Komulainen, Emilia; Zdrojewska, Justyna; Freemantle, Erika; Mohammad, Hasan; Kulesskaya, Natalia; Deshpande, Prasannakumar; Marchisella, Francesca; Mysore, Raghavendra; Hollos, Patrik; Michelsen, Kimmo A.; Mågard, Mats; Rauvala, Heikki; et al. (Frontiers in Cellular Neuroscience, 2014)
Genetic anomalies on the JNK pathway confer susceptibility to autism spectrum disorders, schizophrenia and intellectual disability. The mechanism whereby a gain or loss of function in JNK signaling predisposes to these prevalent dendrite disorders, with associated motor dysfunction, remains unclear. Here we find that JNK1 regulates the dendritic field of L2/3 and L5 pyramidal neurons of the mouse motor cortex (M1), the main excitatory pathway controlling voluntary movement. In Jnk1-/- mice, basal dendrite branching of L5 pyramidal neurons is increased in M1, as is cell soma size, whereas in L2/3, dendritic arborization is decreased. We show that JNK1 phosphorylates rat HMW-MAP2 on T1619, T1622 and T1625 (Uniprot P15146) corresponding to mouse T1617, T1620, T1623, to create a binding motif, that is critical for MAP2 interaction with and stabilization of microtubules, and dendrite growth control. Targeted expression in M1 of GFP-HMW-MAP2 that is pseudo-phosphorylated on T1619, T1622 and T1625 increases dendrite complexity in L2/3 indicating that JNK1 phosphorylation of HMW-MAP2 regulates the dendritic field. Consistent with the morphological changes observed in L2/3 and L5, Jnk1-/- mice exhibit deficits in limb placement and motor coordination, while stride length is reduced in older animals. In summary, JNK1 phosphorylates HMW-MAP2 to increase its stabilization of microtubules while at the same time controlling dendritic fields in the main excitatory pathway of M1. Moreover, JNK1 contributes to normal functioning of fine motor coordination. We report for the first time, a quantitative sholl analysis of dendrite architecture, and of motor behavior in Jnk1-/- mice. Our results illustrate the molecular and behavioral consequences of interrupted JNK1 signaling and provide new ground for mechanistic understanding of those prevalent neuropyschiatric disorders where genetic disruption of the JNK pathway is central.